INOVASI DAN DIGITALISASI LEMBAGA KEUANGAN SYARIAH: STUDI PADA LKMS UKHUWAH BINTANG IHSANI KOTA BENGKULU - Noni Purnama Sari; Gustiya Sunarti; Fatimah Yunus (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to analyze the innovation and digitalization implemented by the Ukhuwah Bintang Ihsani Islamic Microfinance Institution (LKMS) in Bengkulu City and its impact on marketing and customer service. The research method used was a descriptive qualitative approach with a case study. Data were collected through in-depth interviews with management, employees, and customers, supported by documentation studies and direct observation. The results indicate that LKMS Ukhuwah Bintang Ihsani has gradually implemented innovation and digitalization through the use of social media as a marketing tool, digital transaction recording, and online service communication, all while adhering to Sharia principles such as honesty and transparency. This digitalization has had a positive impact on operational efficiency, expanded marketing reach, and increased customer satisfaction and engagement, despite limitations in human resources, digital literacy, and technological infrastructure. The study concludes that innovation and digitalization play a crucial role in strengthening the competitiveness and sustainability of LKMS Ukhuwah Bintang Ihsani. However, strengthening human resource capacity and infrastructure support are necessary for optimal and sustainable Sharia-based digital transformation. Keywords: Innovation, Digitalization, LKMS, Sharia Marketing, Sharia Finance